Designing Instagram Content for Brand Identity and Brand Awareness of Fashion Products (Case Study of Small and Medium Enterprise Vie Collections) - Prasetyo, Dian; Adriantantri, Emmalia; Sasmito, Agung Panji (Transpublika Publisher, 2026)
The development of social media as a digital marketing tool provides opportunities for micro, small, and medium enterprises (MSMEs), particularly in the fashion industry, to build brand identity and increase brand awareness. This study aims to design social media content to strengthen brand identity and enhance brand awareness for Vie Collections MSMEs. The research employs a Research and Development (R&D) method, including needs analysis, product design, expert validation, and product revision. Data were collected through observation, interviews with MSME owners, documentation, and literature studies on branding and digital marketing. The developed products are a Brand Content Kit and a Content Playbook, serving as guidelines for brand identity and social media content management strategies on Instagram. Data analysis used simple qualitative and quantitative descriptive methods, with expert assessment via the Content Validity Index (CVI) method. Results indicate that both the Brand Content Kit and Content Playbook achieved CVI scores in the valid and usable category. The design effectively represents the brand’s character, maintains visual and verbal consistency, and has potential to enhance brand recognition and recall through structured social media content. In conclusion, designing Instagram content through the Brand Content Kit and Content Playbook can serve as a strategic solution for Vie Collections MSMEs to build brand identity and increase brand awareness. Further research is recommended to evaluate the effectiveness of implementation over time and to incorporate additional variables for more comprehensive insights.